2000
DOI: 10.1590/s0301-80592000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica populacional da broca-do-Café Hypothenemus hampei (Ferr.) (Coleoptera: Scolytidae) em Lavras, MG

Abstract: O monitoramento da broca-do-café Hypothenemus hampei (Ferrari, 1867) foi realizado na cultura do café Coffea arabica L., em Lavras - MG, Brasil, no período de janeiro a junho de 1997, com o objetivo de verificar a sua dinâmica populacional na safra da cultura. Delimitou-se uma área experimental de aproximadamente 1500 m² numa lavoura de café, cultivar Catuaí Amarelo, onde foram realizadas amostragens mensais. Foram coletados frutos pendentes, os quais foram examinados quanto a presença de adultos e formas imat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
1
5
0
5
Order By: Relevance
“…Economic losses due to CBB in Brazil have been estimated at $215–358 million annually [ 104 ]. CBB population sizes in Brazil appear to be negatively correlated with rainfall intensity, with the highest population growth occurring during the dry season (May–August) [ 105 , 106 ]. CBB monitoring in robusta (known as conilon in Brazil) [ 107 , 108 ] and arabica [ 109 ] coffee plantations have revealed similar infestation patterns, with peak populations observed at the end of the harvest season (July–August).…”
Section: Insights From Historical Invasions: Indonesia Brazil Etmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic losses due to CBB in Brazil have been estimated at $215–358 million annually [ 104 ]. CBB population sizes in Brazil appear to be negatively correlated with rainfall intensity, with the highest population growth occurring during the dry season (May–August) [ 105 , 106 ]. CBB monitoring in robusta (known as conilon in Brazil) [ 107 , 108 ] and arabica [ 109 ] coffee plantations have revealed similar infestation patterns, with peak populations observed at the end of the harvest season (July–August).…”
Section: Insights From Historical Invasions: Indonesia Brazil Etmentioning
confidence: 99%
“…CBB monitoring in robusta (known as conilon in Brazil) [ 107 , 108 ] and arabica [ 109 ] coffee plantations have revealed similar infestation patterns, with peak populations observed at the end of the harvest season (July–August). Studies elsewhere have also shown a positive correlation between trap catch and berry infestation [ 110 , 111 ], suggesting that traps may be a more cost-effective way to monitor CBB populations and determine an appropriate action threshold or economic injury level that would serve to inform the timing of pesticide applications [ 106 ]. Additionally, several studies have suggested that alcohol-baited traps may be an effective method of control if used at a high density (22–25 traps/ha) [ 64 ] and at the appropriate time in the season when CBB females are actively flying (post-harvest to early fruit growth) [ 112 , 113 ].…”
Section: Insights From Historical Invasions: Indonesia Brazil Etmentioning
confidence: 99%
“…Although we did not detect a significant correlation between meteorological data and the population of H. hampei adults, or percentage of berries attacked, other studies have. In Brazil, it has been shown that populations of the coffee berry borer are negatively related to the increase of rainfall intensity between January and March, and that the growth of the borer population is favored with the onset of the dry season in April, and with high temperatures (Souza & Reis, 1997; Ferreira et al , 2000). However, studies in Africa have shown a positive correlation between the H. hampei adult population and rainfall (Mendesil et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is in this part of the season when H. hampei infestations often tend to decrease. There might be at least two factors contributing to this: (1) harvesting of berries at this part of the year also removes berries infested with H. hampei from the field (Ferreira et al, 2000); and (2) natural B. bassiana infection kills H. hampei.…”
Section: Discussionmentioning
confidence: 99%